Direct costs of interferon‐based and interferon‐free direct‐acting antiviral regimens for the treatment of chronic hepatitis C infection. Issue 9 (21st March 2016) - Gray, E.; O'Leary, A.; Kieran, J. A.; Fogarty, E.; Dowling, T.; Norris, S.; ,
Summary: Given the increasing budget impact of Hepatitis C virus (HCV) treatment, robust real‐world cost data are essential for healthcare decision‐makers to evaluate and understand the costs and benefits of these treatments. To determine the direct cost of treating HCV infection in a hospital‐based ambulatory care setting in Ireland based on available data from the Irish national hepatitis C treatment registry. A microcosting study of the direct costs of patients with hepatitis C treated with interferon‐based and interferon‐free direct‐acting antiviral regimens was conducted. Attendance at the outpatient clinic for clinical assessment, the quantity of resources used per patient, the medication prescribed and the identification and timing of staff involvement was measured and combined to establish a mean cost of treatment per patient and a cost per sustained virological response (SVR). One hundred and sixty‐eight patients were included in the analysis; 119 treated with interferon‐based direct‐acting antiviral regimens and 47 treated with interferon‐free regimens. The mean costs of treatment with the interferon‐based regimens per patient were €38 286 (95% CI €35 305–€41 061). The cost per SVR was €62 457. The mean cost of treatment with interferon‐free regimens per patient was €55 734 (95% CI €50 906–€60 880). The cost per SVR was €81 873. Real‐world cost data provide valuable information to enhance reimbursement decisions. While the direct costs associated with hepatitis C treatment in Ireland are substantial, it is reasonable to expect that the mean cost of treatment and the cost per SVR will reduce as patients with less advanced disease are treated with interferon‐free therapies.